ACUTE RESPIRATORY VIRAL INFECTIONS (ARVI) AND OLD AGE PEOPLE - Saydakhmedov Zukhriddin Ibrkhimjon ugli (Bright Mind Publishing, 2025)
The acute respiratory viral infections (ArVIs) are uncontrollable infections due to high transmissibility, broad spectrum of causative agents, the lack of effective antiviral drugs and vaccination against the majority of these agents (except for influenza virus). Furthermore, the problem of ArVI is of particular importance for elderly people taking into account the frequently occurring decompensation of pre-existing comorbidities due to ArVI that obscures ArVI and affects the course and outcome of the disease. The paper reports data on epidemiology, clinical features, diagnosis, and treatment of ArVI in elderly and senile patients.